2015
DOI: 10.1016/j.jaac.2014.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive-Behavioral Therapy for Child Anxiety Confers Long-Term Protection From Suicidality

Abstract: Objective Evidence for an independent relationship between anxiety and suicidality has been mixed. Few studies have examined this relationship in youth seeking treatment for anxiety. The present study examined the relationship between response to treatment for an anxiety disorder in childhood and suicidal ideation, plans, and attempts at a follow-up interval of 7 to 19 years. We hypothesized that successful treatment for an anxiety disorder in childhood would be protective against later suicidality. Method T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
29
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(32 citation statements)
references
References 44 publications
0
29
0
3
Order By: Relevance
“…As for mood diagnoses, two follow‐ups of a sample of nondepressed, anxious youth previously treated with CBT found that acute treatment outcome was not associated depressive disorders many years later (Benjamin, Harrison, Settipani, Brodman, & Kendall, ; Kendall, Safford, Flannery‐Schroeder, & Webb, ); however, rates of depression 7.4 years following CBT were comparable to lifetime prevalence rates of major depression in the general population (Kendall et al, 2004). Results from the same sample showed that a positive response to CBT predicted lower rates of subsequent suicidal ideation (Wolk, Kendall, & Beidas, ). Overall, research associating youth anxiety treatment with improved mood outcomes has been limited to studies of CBT and with relatively small sample sizes, and has infrequently examined predictors of varied mood outcomes, including suicidal phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…As for mood diagnoses, two follow‐ups of a sample of nondepressed, anxious youth previously treated with CBT found that acute treatment outcome was not associated depressive disorders many years later (Benjamin, Harrison, Settipani, Brodman, & Kendall, ; Kendall, Safford, Flannery‐Schroeder, & Webb, ); however, rates of depression 7.4 years following CBT were comparable to lifetime prevalence rates of major depression in the general population (Kendall et al, 2004). Results from the same sample showed that a positive response to CBT predicted lower rates of subsequent suicidal ideation (Wolk, Kendall, & Beidas, ). Overall, research associating youth anxiety treatment with improved mood outcomes has been limited to studies of CBT and with relatively small sample sizes, and has infrequently examined predictors of varied mood outcomes, including suicidal phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…This high prevalence is of serious concern given that childhood anxiety disorders often run a chronic course, are associated with substantial interference in young peoples' social, educational and family lives, and are a risk for the development of other mental health problems in later life, such as depression 3–5. Effective psychological and pharmacological interventions for childhood anxiety disorders have been established, and early treatment has been found to be associated with lasting benefits, including reduced suicide ideation in adulthood 6. However, relatively few children and adolescents in need access these treatments,7 and of those that do, a significant minority do not benefit 8.…”
Section: Introductionmentioning
confidence: 99%
“…Anxiety disorders affect between 10 and 20% of youth and are associated with numerous adversities, including impaired academic achievement, difficulty with social and peer relations, and increased suicidal ideation . If untreated, anxiety disorders persist into adulthood, placing youth at greater risk for anxiety, depression, substance abuse, educational underachievement, and suicidality . Given the prevalence and impact of youth anxiety disorders, there is public health importance in understanding how to best treat these debilitating disorders.…”
mentioning
confidence: 99%